2003
DOI: 10.1016/s0005-2736(02)00658-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aquaporin 1 and aquaporin 4 water channels in rat choroid plexus

Abstract: The role of aquaporins in cerebrospinal fluid (CSF) secretion was investigated in this study. Western analysis and immunocytochemistry were used to examine the expression of aquaporin 1 (AQP1) and aquaporin 4 (AQP4) in the rat choroid plexus epithelium. Western analyses were performed on a membrane fraction that was enriched in Na(+)/K(+)-ATPase and AE2, marker proteins for the apical and basolateral membranes of the choroid plexus epithelium, respectively. The AQP1 antibody detected peptides with molecular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
84
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 30 publications
10
84
0
1
Order By: Relevance
“…The mRNA expression profile of AQPs in the ovine CP showed 20 times higher expression of AQP1 compared to all isoforms of AQP4. AQP1 was found to be located almost exclusively in the apical membrane of the CP epithelium, which is in agreement with earlier studies that were conducted on rat CPs (Nielsen et al 1993;Speake et al 2003). This localization directly indicates the involvement of AQP1 in the transport of water through the apical membrane of the CP and, therefore, the involvement of AQP1 in CSF production (Owler et al 2010).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The mRNA expression profile of AQPs in the ovine CP showed 20 times higher expression of AQP1 compared to all isoforms of AQP4. AQP1 was found to be located almost exclusively in the apical membrane of the CP epithelium, which is in agreement with earlier studies that were conducted on rat CPs (Nielsen et al 1993;Speake et al 2003). This localization directly indicates the involvement of AQP1 in the transport of water through the apical membrane of the CP and, therefore, the involvement of AQP1 in CSF production (Owler et al 2010).…”
Section: Discussionsupporting
confidence: 89%
“…According to Nielsen et al (1993) these bands may correspond with glycosylated and unglycosylated forms of AQP1, respectively. The localization of AQP4 in the ovine CP, which can be characterized as diffuse in the cytoplasm of epithelial cells, is in line with the findings of Speake et al (2003) and Nazari et al (2015). It has been demonstrated that rat AQP4 has six cDNA isoforms which are differentially expressed in the kidney and brain (Moe et al 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The third reason why the choroid plexuses are considered to the main site of formation should be the fact that the observations mentioned so far were accompanied by a significant number of concurrent studies that pointed to CSF formation by the choroid plexuses (Dandy, 1919;de Rougemont et al, 1960;Pollay et al, 1972;Weed, 1914;Welch, 1963) , and the secretory character of the choroid plexuses was confirmed by the application of the molecular biological methods during the past two decades (Brown et al, 2004;Johanson, 2008;Kanaka et al, 2001;Li et al, 2002;Oshio et al, 2005;Praetorius et al, 2004;Speake et al, 2003;Watts et al, 1991;Zlokovic et al, 1993).…”
Section: Criticism Of the Classic Hypothesis Of Cerebrospinal Fluid Fmentioning
confidence: 97%
“…The secretory character of choroid plexuses that involves pumps, cotransporters and antiporters, ion channels and aquaporins has been confirmed during the past 15 years by the application of molecular biological methods (Brown et al, 2004;Johanson, 2008;Kanaka et al, 2001;Li et al, 2002;Oshio et al, 2005;Praetorius et al, 2004;Speake et al, 2003;Watts et al, 1991;Zlokovic et al, 1993).…”
Section: The Site and The Way Of Cerebrospinal Fluid Formationmentioning
confidence: 98%